2011
DOI: 10.1016/j.jhydrol.2011.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional scaling and inverse distance weighting transform for image processing of hydrogeological structure in rock mass

Abstract: A new imaging method based on the multidimensional scaling (MDS) and inverse distance weighting (IDW) transform is proposed in this study. This method aims to identify, characterize and process an image of the preferential flow path in a rock mass, which strongly governs the hydraulic behavior of this rock mass. This methodology uses pair-wise hydraulic diffusivity data from cross-hole hydraulic testing as the input data. The input data are then processed by MDS and IDW to generate a spatial distribution map o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 30 publications
0
8
0
3
Order By: Relevance
“…Following common practice (e.g. Goovaerts, 2000;Mito et al, 2011;Shi et al, 2016aShi et al, , 2017b, this study sets the value to be 2, and the IDW method turns into the inverse distance squared method.…”
Section: Spatial Interpolation Methodsmentioning
confidence: 99%
“…Following common practice (e.g. Goovaerts, 2000;Mito et al, 2011;Shi et al, 2016aShi et al, , 2017b, this study sets the value to be 2, and the IDW method turns into the inverse distance squared method.…”
Section: Spatial Interpolation Methodsmentioning
confidence: 99%
“…The power β The power β in equation (10) is a key parameter in computing spatially-distributed meteorological variables, and is normally set to be 1 or 2 (e.g. Gotway et al 1996, Nalder and Wein 1998, Mito et al 2011. However, Husar and Falke (1996) indicated that a smoother result for integration can be obtained with a higher power value and Gotway et al (1996) proved that the accuracy of the IDW method tended to increase along with the power increase.…”
Section: Parameters For Integrating Meteorological Variablesmentioning
confidence: 99%
“…where N is the number of used meteorological stations, P p is the interpolated value at the place of interest, P i is the value at the i-th given station, D i is the distance from the i-th given station to the place of interest, and β is the power of D i . Following common practice (e.g., Goovaerts, 2000;Mito et al, 2011;Shi et al, 2016aShi et al, , 2017, this study adopted the value β to be 2, and the IDW method turns into the so-called inverse distance squared method.…”
Section: Spatial Interpolation Methodsmentioning
confidence: 99%